2012
DOI: 10.1158/1538-7445.am2012-1885
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1885: Targeting the FOXO1/KLF6 transcriptional network to modulate response to anti-EGFR based therapy

Abstract: Epidermal growth factor receptor (EGFR) activation is both a key molecular driver of disease progression and the target of a broad class of molecular agents designed to treat advanced cancer. Nevertheless, resistance develops through several mechanisms including constitutive activation of AKT signaling. Additional molecular characterization of the downstream mediators of EGFR signaling may lead to the development of new classes of targeted molecular therapies to treat resistant disease. Here we identify a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other research indicated that reduced KLF6 expression levels in lung and prostate cancers have been reported to be correlated with increased likelihood of recurrence ( 23,24 ). Activation of KLF6 triggered transactivation of p21 and EGFR and suppressed cyclin D1 (CCND1)-induced cell proliferation and EGFR-induced cell invasion/metastasis ( 25–27 ). KLF15 has recently been implicated in the development of several human malignancies, including breast cancer ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other research indicated that reduced KLF6 expression levels in lung and prostate cancers have been reported to be correlated with increased likelihood of recurrence ( 23,24 ). Activation of KLF6 triggered transactivation of p21 and EGFR and suppressed cyclin D1 (CCND1)-induced cell proliferation and EGFR-induced cell invasion/metastasis ( 25–27 ). KLF15 has recently been implicated in the development of several human malignancies, including breast cancer ( 28 ).…”
Section: Discussionmentioning
confidence: 99%